Software 'Enabled' Research? Fears, Hopes, and Some 'New Vistas for Social Science Research in Africa - Kikooma, Julius F. (Phantom Solutions, 2005)
Computerizing qualitative research over two decades ago transformed the way social scientists could experiment with electronic manipulation of textual data based on the application of existing programs and approaches. There is however legitimate concerns about the effects of technology on practice that help define the problems to be addressed in computerizing research. Such concerns point yet to another example of a deeper issue raising such questions as: Is the software just a tool or does it in some way drive the research? Or whether specific software favours or precludes particular research methods. While reflecting on my own experiences with using one of the software programs-namely NVivo, my second aim is to critique the typical sentiments that software is simply and innocent research tool for the social scientist all too often missing, ignoring or leaving out important debates in the research community. The implications of the strategies adopted in this study are that unlike the situation just a decade ago, qualitative researchers now have available to them, an array of software tools to assist their research, and the use of software - including, but not limited to, word processors- seems more and more to be a regular part of the qualitative research process.
Keywords: software; qualitative research; methods; social sciences